The Historical Narration between the science and Ideology. Acusations, Replications and some Proposals that Overcomes the Conflict (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This article attempts to be an approach to foremost questions in regard to the way history reconstructs the past. This will consider the perspectives of certain authors on this matter, especially those pertaining to Italian micro history.  A narration is to surpass other tales developed in institutions of historical production, which have been influenced by politico-ideological interests.The posting of these questions is linked to the intent of finding answers to some refutations from the viewpoint of historians.  This questions the capacity of history to provide rational and coherent explanations about past societies.
Keywords: Argentinian History; Argentinian literature; ideology; memory